1992
DOI: 10.1111/j.1365-2559.1992.tb00346.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the EBV latent membrane protein (LMP‐1) is independent of CD23 and bcl‐2 in Reed‐Sternberg cells in Hodgkin's disease

Abstract: A series of 33 cases of Hodgkin's disease was investigated for the presence of the EBV encoded latent gene product LMP-1 and of CD23 using iminunohistochemical techniques. The expression of bcl-2 was examined in a subset of cases. LMP-1 was detected in the Reed-Sternberg'cells in 15 cases, Although LMP-1 is known to upregulate CD23 and bcl-2, there was no correlation between the expression of LMP-1 and the detection of CD23 and bcl-2 in Reed-Sternberg cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…None of our Med-DLBCL were positive for EBER and although rare RS cells were positive for both CD23 and EBER in 1 CHL case, we are unable to confirm any positive relation between EBER and CD23 expression given the lack of CD23 expression in the other four EBER positive CHL cases and the lack of EBER in the other CD23 positive CHL case. In agreement with our study, Armstrong et al 25 reported CD23 expression by RS cells in 2 of 11 CHL cases that was independent of EBV infection. In contrast, Sandvej et al 26 reported higher CD23 expression by RS in 8/27 cases.…”
Section: Discussionsupporting
confidence: 93%
“…None of our Med-DLBCL were positive for EBER and although rare RS cells were positive for both CD23 and EBER in 1 CHL case, we are unable to confirm any positive relation between EBER and CD23 expression given the lack of CD23 expression in the other four EBER positive CHL cases and the lack of EBER in the other CD23 positive CHL case. In agreement with our study, Armstrong et al 25 reported CD23 expression by RS cells in 2 of 11 CHL cases that was independent of EBV infection. In contrast, Sandvej et al 26 reported higher CD23 expression by RS in 8/27 cases.…”
Section: Discussionsupporting
confidence: 93%